(untitled) (Global Journal of Medical Research, 2020)
In Japan, many food poisoning cases occur every year form the rainy season to summer. After all, restaurants account for about 50% of all food poisoning cases. Still they also occur at school meals (6.4%) and hospitals (0.6%), where hygiene management should strictly controlled in the Ministry of Health, Labor, and Welfare announced (2019). Therefore, from the viewpoint of food poisoning prevention, this study focused on the stove knob and water faucet, which are often touched by the cook’s fingers in the kitchen and may cause secondary contamination. The effect of hygiene education investigated by measuring invisible microbial load as visible ATP value using ATP wiping test. The 12 stove knob and 11 water faucet inspected before and after hygiene education by using the ATP wiping test. Before hygiene education, the average value of the ATP values measured after washing before and after washing. To the surprise, after washing, the ATP value did not drop below 1000 for Stove knob and Water faucet. Almost the same ATP value as before cleaning.